Теоретико-методологічні засади дослідження сфери охорони здоров’я метрополій в умовах сталого розвитку - Корнійчук, О.П. (Економіка природокористування і сталий розвиток, 2020)
Розкрито теоретико-методологічні засади дослідження впливу охорони здоров’я метрополій на інфраструктуру цієї сфери на прикладі трьох зон тяжіння до них в умовах пріоритетності сталого розвитку. The article describes the theoretical and methodological principles of the study of the impact of metropolitan health care on health infrastructure in three zones of gravity under conditions of priority of sustainable development in order to provide quality and affordable medical care. The first – up to 15 km – at the community level; the second – up to 50 km – at the level of hospital districts; the third – up to 250–300 km – at the interregional level. Unlike EU countries, Ukraine lacks the proper legislative and governmental institutionalization of metropolitan areas and regulates their impact on medical infrastructure in the abovementioned areas of gravity. In our view, the metropolitan medical space is an organized and controlled through the Regional Department of Health, the Ministry of Health of Ukraine, the National Academy of Medical Sciences of Ukraine, local self-government and departments the infrastructure of provision of preventive (PRMС), primary (PMС), secondary (TMС), tertiary (TMС), emergency (NMС), emergency (EMС), palliative and hospice (PHС) and rehabilitation (RMС) medical care within the responsibilities of communities, districts and regions with a well-established system of statistical and economic reporting. The metropolitan function in health care is a complex of TMС, PIC, RMС services that provide patients with 1–3 gravity zones and in other regions based on high integration into the existing health care network both in the region and beyond. the purpose of accumulated control of information and financial space. On the other hand, the metropolis healthcare sector in the metropolitan environment is the process of strengthening the vertical and horizontal integration of healthcare institutions – PMС, PMС, Specialized Medical Assistance (SMA) and EMС without merging them with eHealth-based TMС medical institutions, The National Health Service of Ukraine (NHSU), due to the intensity and nature of labor migration from suburban areas.